Pencegahan Hipertensi pada Lansia di Desa Mojosari Puskesmas Modopuro, Mojokerto - Khamidah, Nur; Gunawan, Yoga Chandra; Sari, Dwi Arifta Yunita; Ourvalica, Vira Setya; Husna, Farizah El; Sulfy, Rindang Arina; Sedana, I Ketut Gede Toya; Dewi, Ni Putu Ayu Yusita; Prasetyoadi, Teofilus Dani (PENITI BANGSA (Pemanfaatan Ilmu Pengetahuan dan Teknologi bagi Masyarakat), 2025)
Hypertension is one of the health problems because hypertension is one of the entry points or risk factors for diseases such as heart disease, kidney failure, diabetes mellitus, and stroke. The elderly have a higher risk of suffering from hypertension than those who are younger. With the highest risk of hypertension in the elderly, good and informative education is needed to prevent hypertension in the elderly. This study was conducted to determine the extent of the elderly's knowledge and satisfaction regarding information about hypertension provided by health workers at the Modopuro Health Center, Mojokerto Regency. The study was conducted by providing education to the elderly and then giving questions with the answer choices Yes and No to determine the extent of the elderly's knowledge about hypertension. There were 26 participants who were mostly elderly. . Overall respondents (100%) were satisfied with the health services related to hypertension at the health facility. Respondents' knowledge about hypertension is very good. This is shown in the distribution of correct answers above 75%. Among the ten questions asked by the author, there are still many respondents (23.1%) who still do not know that prolonged stress and excessive salt can also trigger high blood pressure. While in other question items, more than 80% of respondents have known various things about hypertension. Thus, this study succeeded in providing education about hypertension to the elderly at the Modopuro Health Center, Mojokerto Regency.